A Cascade‐Reaction Nanoreactor Composed of a Bifunctional Molecularly Imprinted Polymer that Contains Pt Nanoparticles. Issue 20 (1st April 2015) - Wang, Jiao; Zhu, Maiyong; Shen, Xiaojuan; Li, Songjun
Abstract This study was aimed at addressing the present challenge of cascade reactions, namely, how to furnish the catalysts with desired and hierarchical catalytic ability. This issue was addressed by constructing a cascade‐reaction nanoreactor made of a bifunctional molecularly imprinted polymer containing acidic catalytic sites and Pt nanoparticles. The acidic catalytic sites within the imprinted polymer allowed one specified reaction, whereas the encapsulated Pt nanoparticles were responsible for another coupled reaction. To that end, the unique imprinted polymer was fabricated by using two well‐coupled templates, that is, 4‐nitrophenyl acetate and 4‐nitrophenol. The catalytic hydrolysis of the former compound at the acidic catalytic sites led to the formation of the latter compound, which was further reduced by the encapsulated Pt nanoparticles to 4‐aminophenol. Therefore, this nanoreactor demonstrated a catalytic‐cascade ability. This protocol opens up the opportunity to develop functional catalysts for complicated chemical processes.